Escapism or Integration? Family Constellations Reflecting on the Leisure-Time Physical Activity of Adults, Leisure Sciences - Leino Henna M.; Hurmerinta Leila; Sandberg Birgitta; Kokko Sami; Lyytimäki Jari; Tapio Petri; Vasankari Tommi (Taylor & Francis, 2025)
Insufficient physical activity is an increasing threat to personal well-being and public health. While significant research has focused on the factors that encourage or restrict physical activity, the impact of family constellations on physical activity remains under-researched despite its evident impact on leisure-time physical activity (LTPA). This study aims to analyze how being embedded in a family constellation reflects on LTPA. Our data are drawn from interviews with 89 working adults living in a household with a spouse and/or children. The results indicate that individuals have both escapist and integrative motivations for LTPA, which reflect particular family constellations. This finding leads to the following LTPA dimensions: solitary escapism, co-escapism, integrative escapism, and integration. Furthermore, the mechanism is bidirectional: family affects LTPA, and LTPA reflects on personal and family well-being. Public and private actors can utilize these findings when compiling policies and recommendations and developing services intended to increase LTPA.